Analisis Penerapan Activity-Based Costing Tindakan Debridemen Bedah pada Diagnosis Tunggal di Kamar Operasi RSKD Duren Sawit Tahun 2022 - Zakaria, Reynaldi Fattah; Nadjib, Mardiati (Jurnal Ekonomi Kesehatan Indonesia, 2024)
In 2022, RSKD Duren Sawit has officially held operating room services. The demand for more comprehensive operating room services increased rapidly. The temporary operating room rates were set by adapting the rates of other regional hospitals and the Governor of DKI Jakarta's regulations. There is a huge difference in costs between the hospital rates and the INA-CBGs claim rates, especially for surgical debridement performed in the operating room. One of the factors causing the difference is the undetermined cost for debridement based on the unit cost component. Knowing the unit-cost debridement in the operating room according to the cost per activity. The study design was a retrospective cohort. Debridement action activities were collected through direct observation and patient operation reports. Then perform unit cost calculations based on activity-based costing. The unit cost of debridement with spinal anesthesia is Rp2.841.511,00. The unit cost calculation results are lower than hospital rates for neck debridement and mediastinitis. However, for debridement by general surgery and oral surgery, the unit cost is higher.